Polypharmacy is a challenge for our generation, and the knowledge of deprescribing is a needed skill of our health care professionals - Shadi Sarahroodi (German Journal of Pharmaceuticals and Biomaterials, 2022)
Life expectancy has risen dramatically in accordance with human society's progress and our access to new treatments and therapies. As a result, the old population has grown significantly. "Polypharmacy" is defined as taking five or more medications regularly, and "Hyper-polypharmacy" is defined as using more than ten medications on a regular basis. Elderly persons and others with chronic illnesses need to see multiple doctors and take various medications. As a result, polypharmacy in this society is a severe concern, ranging from 10% to 90% in various populations and, unfortunately, on the rise. Polypharmacy is frequently linked to adverse drug reactions (ADR), drug interactions, falls, prescribing cascades, patient non-adherence to medications, and even more severe outcomes such as hospitalisation and death. To deal with polypharmacy, we must analyse our patients and their medications to develop and implement a strategy for discontinuing or lowering medications that are no longer helpful or may be harmful. This procedure is known as "Deprescribing". Our health care professionals, particularly physicians and pharmacists, must become familiar with it and have sufficient knowledge of its set protocols to participate in it and reduce patient damage. The issue of polypharmacy and its numerous consequences for society (especially elderly patients) and the deprescribing process are covered in this article.